Case report: Cardiac metastatic leiomyoma in an Asian female - Li, Juan; Zhu, Hong; Hu, Shuang-Ye; Ren, Shang-Qing; Li, Xing-Lan (Frontiers in Surgery, 2022)
Background: Uterine leiomyomas are the most common gynecological tumors in women of child-bearing age and premenopausal women, while benign metastasizing leiomyomas of the heart are rare. Case presentation: We report a rare case of metastasizing leiomyoma in the heart of a 54-year-old woman 10 years after a uterine leiomyoma was discovered during hysterectomy. Echocardiography, cardiac plain scan and enhanced MRI at presentation showed a soft tissue signal mass in the right ventricle. A large cardiac mass attached to the chordae of the tricuspid valve and later shown to be histopathologically consistent with uterine leiomyoma was successfully resected through a right atriotomy. Conclusions: Our case report highlights a rare type of tumor of the heart and suggests that metastasizing leiomyoma should be considered in the differential diagnosis of right-sided cardiac tumors.The complete surgical resection of the tumor was considered to be the best treatment.